Casing strength degradation in thermal environment of steam injection wells - Hidayat, M.I.P. (Institute of Physics Publishing, 2016)
Degradation of the casing strength in relation with thermal cycles of steam injection process is still less explored in literature. In this paper, three-dimensional finite element (FE) analysis of casing strength degradation in thermal environment of steam injection wells is presented. 3D FE models consisting of casing-cement-formation system are developed in this study. Grade N80 casing is employed with the casing length of 3.048 m. In the analysis, cyclic thermal stresses induced on the casing in thermal environment of steam injection wells from 25 °C to 360 °C are first examined to verify the feasibility of the 3D FE models. Degradation of the casing strength in the thermal environment is subsequently investigated by applying an external pressure that represents formation pressure to the casing-cement system. The results show that the casing capability to resist the pressure is lowering as the number of thermal cycles extends, thus causing casing strength degradation in the thermal application. It is also shown that the casing may fail under external pressure below its specified collapse strength i.e. 10 lower than the reference casing strength obtained at 360 °C.